2017
DOI: 10.1038/srep42530
|View full text |Cite
|
Sign up to set email alerts
|

Plasmonic nanomeshes: their ambivalent role as transparent electrodes in organic solar cells

Abstract: In this contribution, the optical losses and gains attributed to periodic nanohole array electrodes in polymer solar cells are systematically studied. For this, thin gold nanomeshes with hexagonally ordered holes and periodicities (P) ranging from 202 nm to 2560 nm are prepared by colloidal lithography. In combination with two different active layer materials (P3HT:PC61BM and PTB7:PC71BM), the optical properties are correlated with the power conversion efficiency (PCE) of the solar cells. A cavity mode is iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
128
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 225 publications
(136 citation statements)
references
References 57 publications
4
128
0
4
Order By: Relevance
“…These nanohole arrays can support SLRs and are typically fabricated by transferring hexagonally ordered arrays of polystyrene particles from an air/water interface onto substrates, followed by etching of the particles before depositing the metal. Stelling et al have systematically examined such silver nanomeshes regarding their plasmonic properties by varying the particle sizes and thereby the size of the holes over a broad range and supporting their results with FDTD simulations . In a more recent publication, Torrisi et al have shown an application for these nanomeshes as an intralayer film between transparent conductive oxides (TCO).…”
Section: Plasmonic Lattices Via Colloidal Assemblymentioning
confidence: 91%
“…These nanohole arrays can support SLRs and are typically fabricated by transferring hexagonally ordered arrays of polystyrene particles from an air/water interface onto substrates, followed by etching of the particles before depositing the metal. Stelling et al have systematically examined such silver nanomeshes regarding their plasmonic properties by varying the particle sizes and thereby the size of the holes over a broad range and supporting their results with FDTD simulations . In a more recent publication, Torrisi et al have shown an application for these nanomeshes as an intralayer film between transparent conductive oxides (TCO).…”
Section: Plasmonic Lattices Via Colloidal Assemblymentioning
confidence: 91%
“…where ζ ∈ [0, 1] is the duty cycle, ε m (λ 0 ) is the permittivity of Mo [38], and ε d (λ 0 ) is the permittivity of Al 2 O 3 [33]. Spectrums of real and imaginary parts of the relative permittivity ε(λ 0 )/ε 0 of MgF 2 [31], AZO [33], iZnO [34], CdS [36], Al 2 O 3 [37], and Mo [38] used in our calculations are displayed in Fig. 2.…”
Section: Optical Description Of Solar Cellmentioning
confidence: 99%
“…Besides the template fabricated through photolithography, the periodic or random arranged microspheres on substrate can also act as the template for the deposition of metal film with micrometer size holes, which allow the penetration of light . Thin film with the formation of cracks inside, in most cases, is normally regarded as poor quality.…”
Section: The Front Metal Electrodementioning
confidence: 99%
“…The Au nanomesh induced plasmonic effects has improved the short‐circuit current density ( J SC ) from 7.02 to 14.2 mA cm −2 . As shown in Figure a, the periodicities of the Au nanomesh can be modulated to excite surface plasmon at different resonant wavelengths, which can selectively improve the light absorption of active layer . Figure b is the cross‐sectional SEM image of the representative Au nanomesh incorporated OSCs .…”
Section: The Front Metal Electrodementioning
confidence: 99%
See 1 more Smart Citation